Tsalsol /Chain Rhyme - Elham Zadafshar (مطالعات زبانی و بلاغی)
The fundamental tools of literary assessment and aesthetics must be sought in rhetorical studies. Although these studies do not engage in the critique and evaluation of literary works in practice, and only suffice to define, identify, cite evidence, and express theoretical opinions, they still provide means for better and more accurate evaluation of literary works. As a rhetorical device, the interlocking or chain rhyme which is called Tasalsol in Persian poetry, can be observed in both verbal and conceptual continuity of verses. It is one of the techniques mentioned in rhetorical books and treatises in certain periods of Persian poetry, yet it does not stand out in modern rhetorical books. Persian chain rhyme scope links it to some other devices and genres. For example, one type of conceptual interlocking rhyme is Tasalsol Mowqouf, which is related to the use of the technique in run-on lines and enjambment. Another type of verbal chain rhyme is mostly observed in Qasida, a Persian subgenre similar to ode, and has been referred to as chain ode in the existing scholarship. This latter type closely resembles the Persian literary device, Taqsim which is somehow a sequence of parallel attribution, referred to as serial Taqsim in some ancient sources. Moreover, this type of Taqsim overlaps with some other Persian devices such as Rad ol-Ajz ala al Sadr and Rad ol-Sadr ala al Ajz, Tashabah ol-Atraf, Tekrar or Mokarar. In this article, we will delve into the examination of this device and its examples.